Speech by Brig. Gen. Dato’ Prof. Dr. Kamarudin Hussin UniMAP’s Vice Chancellor during Yemenis Welcoming Dinner - Kamarudin, Hussin, Brig. Gen. Dato’ Prof. Dr. (Universiti Malaysia Perlis, 2010)
Event was held at Hotel Putra Palace, Kangar, Perlis.